Implementation of Sustainable Reforms in the Indian Automotive Industry: From Vehicle Emissions Perspective. Issue 1 (31st December 2022) - Borkhade, Revati; Bhat K, Subrahmanya; Mahesha, GT
Abstract: The scenario of the Automobile Industry has changed, not only in India but also for the world as a whole. Rise in demand for more sustainable mobility and vehicles with increased usage of renewable energies have given rise to a revolution. This revolution has not only been affecting mankind for better implementation of resources but has also shown tremendous greener and cleaner effects on the flora and fauna of the land as a whole. There has been electrification of vehicles, addition of superior systems to generate lesser harmful effluents and also changing the guidelines of emissions to cleaner and more sustainable ones. The purpose of this paper is to review and state the existence of different pieces of literature for the transition from Bharat Stage-IV (BS-IV) to Bharat Stage-VI (BS-VI). Much has been written about the transition to BS-VI, the difficulties, and the positive effects on vehicle reliability, economy and the environment. In particular, this work explores the parallels between BS-VI and the corresponding Euro norms and their sequence of implementation. The aforesaid transition has increased the number of oil refineries in India that produce BS-VI-compliant fuels, keeping in mind the increased need for it. This paper explores the current state of the literature and throws light on many of the questions regarding this significant transition. The authors have tried to study the ongoing issues including the stress of inventory management of diesel-run passenger cars, the different refinements required to process and manufacture the BS-VI-compliant vehicles, people's reaction on the changes brought in by the issuing bodies with respect to the norms, to name a few. The focus of the research has been on Bharat Stage emission norms, their implementation challenges and automobile pollution in India to name a few. The authors also discuss the needs, advantages and challenges faced by the industry, producers and customers and conclude that this change is one of the reasons for the decline in car sales in India as it may affect the buying power of the customers.